RISKS OF KNOWLEDGE SOCIETY AND MEGATECHNOLOGIES - Оноприенко, В. И. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
Backgrounds of the risk society are directly related to the growth of scientific knowledge and the empowerment of scientific and technological activities as an important factor of social transformation. There were attempted to assess possibilities of risks of the emerging knowledge society, in particular its megatechnologies, that radically change ontological characteristics of socio-cultural reality, ideology and human worldview.